Promosi Melalui Media Sosial untuk Meningkatkan Pembelian Produk di Prima Freshmart Surabaya - Frida Fabriane; Nuriah Yuliati; Risqi Firdaus Setiawan (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The development of science and technology has changed people's lifestyles and consumption patterns quickly and practically, one of which is by consuming frozen food products. Prima Freshmart (PFM) is a specialty store that sells fresh, processed and ready-to-eat food ingredients derived from chicken products, such as frozen food. PFM is part of Charoen Pokphand Food (CP Food). The Indonesian Internet Service Providers Association Survey (APJII) stated that Internet users in Indonesia in 2014 reached 88.1 million users or about 34.9 percent of the total population of Indonesia. In addition, with the increasing number of competitors of similar companies and the unknown Prima Freshmart as a whole, consumer buying interest is still low. Therefore, the purpose of this study is to determine the effectiveness of social media promotion in introducing Prima Freshmart, to analyze the influence of social media on product purchases at Prima Freshmart. The method used in data collection is by observation, distributing questionnaires and interviews. The analysis used is the EPIC model to determine the effectiveness, and multiple linear regression analysis to determine the effect of social media in introducing Prima Freshmart. The results showed that the results of measuring the effectiveness of promotions with the EPIC Model showed the final result of the EPIC rate value was 3.92 which was included in the effective category. As for the results of multiple linear regression analysis on the t-test for social media websites of 0.282 > 0.05, on social media Instagram of 0.000 < 0.05, and on social media WhatsApp of 0.021 < 0.05. for the f test value, the significance value is 0.000 <0.05, which means that all independent variables jointly affect purchasing decisions. Meanwhile, for the determination test the R Square value is 0.55 which means that purchasing decisions are influenced by social media websites, Instagram, and WhatsApp by 55.5% and the remaining 44.5% is influenced by other variables not examined.